A clinical study to evaluate the safe and effective use of a new, single use stethoscope cover to enable reduction in pathogen transmission during auscultation - Nazari-Shafti, Timo Z.; Meyborg, Heike; Iske, Jasper; Schloss, Maximilian; Seeber, Fabian; Friedrich, Aljona; Exarchos, Vasileios; Richter, Anja; Falk, Volkmar; Emmert, Maximilian Y. (Frontiers in Medicine, 2023)
Objectives: Stethoscopes carry a significant risk for pathogen transmission. Here, the safe use and performance of a new, non-sterile, single-use stethoscope cover (SC), that is impermeable for pathogens, was investigated by different healthcare professionals (HCPs) in the postoperative care setting of an intensive care unit (ICU). Methods: Fifty-four patients underwent routine auscultations with the use of the SC (Stethoglove®, Stethoglove GmbH, Hamburg, Germany). The participating HCPs (n=34) rated each auscultation with the SC on a 5-point Likert scale. The mean ratings of acoustic quality and the SC handling were defined as primary and secondary performance endpoint. Results: 534 auscultations with the SC were performed (average 15.7/user) on the lungs (36.1%), the abdomen (33.2%), the heart (28.8%) or other body-sites (1.9%). No adverse device-effects occurred. The acoustic quality was rated at 4.2±0.7 (mean) with a total of 86.1% of all auscultations being rated at least as 4/5, and with no rating as below 2. The SC handling was rated at 3.7±0.8 (mean) with a total of 96.4% of all auscultations being rated at least 3/5. Conclusions: Using a real-world setting, this study demonstrates that the SC can be safely and effectively used as cover for stethoscopes during auscultation. The SC may therefore represent a useful and easy-to-implement tool for preventing stethoscope-mediated infections.